2010
DOI: 10.1161/strokeaha.109.560342
|View full text |Cite
|
Sign up to set email alerts
|

Vasa Vasorum and Plaque Neovascularization on Contrast-Enhanced Carotid Ultrasound Imaging Correlates With Cardiovascular Disease and Past Cardiovascular Events

Abstract: Background and Purpose-Histological data associate proliferation of adventitial vasa vasorum and intraplaque neovascularization with vulnerable plaques represented by symptomatic vascular disease. In this observational study, the presence of carotid intraplaque neovascularization and adventitial vasa vasorum were correlated with the presence and occurrence of cardiovascular disease (CVD) and events (CVE). Methods-The contrast-enhanced carotid ultrasound examinations of 147 subjects (mean age 64Ϯ11 years, 61% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
2
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(169 citation statements)
references
References 29 publications
(33 reference statements)
8
145
2
9
Order By: Relevance
“…Systematic histopathological validation revealed a direct positive correlation between contrast enhancement using this semi-quantitative grading scale and histology [44,45]. Furthermore, wholly consistent with the concept that more vulner- able plaque contains a higher degree of neovascularization, recent retrospective studies revealed the association between plaque enhancement on contrast-enhanced ultrasound imaging and clinical symptoms including cerebrovascular events in patients with carotid atherosclerosis [19,46,47]. Therefore, contrast-enhanced ultrasound examination of the carotid artery may provide a novel, noninvasive clinical tool to identify and quantify the presence and the extent of arterial plaque neovascularization in patients at risk for developing symptomatic atherosclerosis, thus permitting more reliable assessment of cardiovascular risk.…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Imsupporting
confidence: 56%
See 1 more Smart Citation
“…Systematic histopathological validation revealed a direct positive correlation between contrast enhancement using this semi-quantitative grading scale and histology [44,45]. Furthermore, wholly consistent with the concept that more vulner- able plaque contains a higher degree of neovascularization, recent retrospective studies revealed the association between plaque enhancement on contrast-enhanced ultrasound imaging and clinical symptoms including cerebrovascular events in patients with carotid atherosclerosis [19,46,47]. Therefore, contrast-enhanced ultrasound examination of the carotid artery may provide a novel, noninvasive clinical tool to identify and quantify the presence and the extent of arterial plaque neovascularization in patients at risk for developing symptomatic atherosclerosis, thus permitting more reliable assessment of cardiovascular risk.…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Imsupporting
confidence: 56%
“…Shah et al used a semi-quantitative grading scale (grade 0 = no neovascularization, grade 1 = limited neovascularization, grade 2 = moderate neovascularization, grade 3 = pulsating, arterial vessel) to provide a distinction between the variations observed in intraplaque neovascularization [44]. Using a similar, dichotomous grading system, various recent studies categorized contrast-enhanced ultrasound enhancement as no contrast effect (grade 1) or high (grade 2) based on the visual detection of the contrast effect within the plaque [46]. Systematic histopathological validation revealed a direct positive correlation between contrast enhancement using this semi-quantitative grading scale and histology [44,45].…”
Section: Plaque Neovascularization On Contrast-enhanced Ultrasound Immentioning
confidence: 99%
“…Plaque inflammation and neovascularization are histological markers of vulnerable plaques and predictors of unstable atherosclerotic lesions in patients with cerebro-or cardiovascular disease (17). This has led to increasing interest in the inflammatory and histological processes that occur in atherosclerotic lesions and give rise to cerebrovascular events (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…It combines the high spatial and temporal (15). CEUS reveals plaque biological activity and vascularization in vivo and a number of studies have suggested that CEUS may be useful for plaque risk stratification and assessing atherosclerosis progression and regression (13,16,17). However, to the best of our knowledge, no studies have directly compared the effectiveness of CEUS with standard ultrasonography for assessing plaque neovascularization in patients at risk of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…(Anderson et al, 2011;Lindner et al, 2000 ;ten Kate et al, 2010). Staub et al (2010a) demonstrated that adventitial vasa vasorum and plaque neovascularization of the carotid artery correlated with cardiovascular disease and past cardiovascular events using contrast-enhanced ultrasound in a retrospective study of 147 patients. Neovascularization or angiogenesis is also found in relation to AAA (Herron et al, 1991;Holmes et al, 1995;Thompson et al, 1996).…”
Section: Functional and Molecular Imagingmentioning
confidence: 98%